Determinants of the duration of economic recoveries: The role of "too much finance" - Vítor Castro; Boris Fisera (Charles University in Prague, Institute of Economic Studies (IES), 2022)
This paper explores the effect of financial development on the duration of economic recoveries, considering a sample of 414 economic recoveries observed in 67 countries during the period 1989-2019. We define the duration of economic recovery, as the time it takes the economy to return to its potential output level. Using a continuous-time Weibull duration model, we find that a higher level of financial development tends to prolong the duration of economic recovery. Therefore, our findings indicate that a too highly developed financial system might delay a full recovery after a recession, supporting the notion that there is "too much finance". In particular, greater size of the underregulated sector of non-banking financial institutions (shadow banks) prolongs the economic recovery. Moreover, the emerging economies, with their generally poorer regulatory frameworks, are more negatively affected by "too much finance". Underlining the importance of an effective regulation of the entire financial system, our results also confirm that a higher regulátory quality limits the negative consequences of "too much finance".
Keywords: F10; F30; F31; F43; 330; economic recovery; duration analysis; Weibull duration model; financial development; too-much-finance